Attitudes and perceptions of Ilonggo households and enterprising power towards microfinance institutions and their lending preferences - Diano, Pearl Gladys; Noble, Celiryn; Somido, Reynaldo; Valencia , Arlen
The microfinance industry in the Philippines has been growing wherein enterprising poor and low-income households are able to raise their income levels and improve their living standards through a broad range of financial services such as loans. With the readily available funds provided by microfinance institutions, the enterprising poor are able to sustain their livelihood and businesses such as sari-sari store, food vending, farming, and other household-based enterprises.However, informal lending sources such as 5-6 are also able to provide financial services and are availed regardless of their usurious rates. The aim of this research is to understand the Ilonggo household characteristics and identify the factors that influence the credit decisions of the enterprising por. Quantitative and qualitative approaches were considered to carry out the objectives. The results showed that the loan availed from microfinance institutions are solely for rotating capital of their livelihood and businesses to have a steady income that is then used to repay the loan and finance the household expenses. Factors such as household income, age, marital status, and educational attainment are not significant in the credit decisions such as loan source and amount of loan.